Średniowieczne "clausulae" różańcowe i ich teologiczna treść = Medieval Clausulae of Rosary and Their Theological Content - Lekan, Janusz (2024)
This theological reflection focuses on one form of Marian devotion, the Rosary. This prayer, which has been known for centuries, has a deep theological meaning: it introduces the mysteries of salvation (doctrine) and is a form of meditative prayer (spirituality). As a prayer, it also needs renewal, as encouraged by Pope Paul VI in his exhortation Marialis cultus. The medieval forms of Clausular Rosary could become a way of renewing this prayer. However, before the historical and theological context of its origin is shown, it is necessary to point out the nature of Marian devotion and its place in Christian piety. After discussing the historical and theological context of how the clausulae were formed and the role of Dominic of Prussia in this process, the actuality of this prayer shall be emphasised by pointing out its theological richness: its biblical and contemplative value. The Clausular Rosary also has ecumenical value, since this form of prayer has strictly biblical roots: it contains the Angelic Salutation described in the Gospel of St. Luke and a reference to the mysteries of salvation accomplished by Jesus Christ. It is also a response to the popularity of meditation in the spirit of Eastern religions.
Celem tej refleksji teologicznej jest skupienie się na jednej z form kultu maryjnego, jaką jest różaniec. Modlitwa ta, znana od wieków, posiada bogate znaczenie teologiczne – wprowadza w mis-terium zbawienia (doktryna) i stanowi rodzaj modlitwy medytacyjnej (duchowość). Jest modlitwą, która potrzebuje również odnowy, do czego zachęca papież Paweł VI w adhortacji Marialis cultus. Jedną z dróg odnowy tej modlitwy mogą stać się średniowieczne formy klauzuli różańcowych. Zanim jednak zostanie ukazany historyczny i teologiczny kontekst jej powstania, trzeba wskazać na naturę kultu maryj-nego i jego miejsce w pobożności chrześcijańskiej. Po omówieniu kontekstu historyczno-teologicznego powstawania klauzul i roli Dominika z Prus w tym procesie, zechcemy podkreślić aktualność tej mod-litwy, wskazując na jej bogactwo teologiczne – wartość biblijną i kontemplacyjną. Różaniec klauzulowy ma również wartość ekumeniczną, gdyż ta forma modlitwy posiada ściśle biblijne korzenie, zawiera bow-iem Pozdrowienie anielskie, opisane w Ewangelii św. Łukasza i odniesienie do tajemnic zbawienia dokona-nego przez Jezusa Chrystusa. Jest także odpowiedzią na modę medytacji religii Wschodu.
Keywords: Adolf of Essen; Christ; Dominic of Prussia; Marialis Cultus; Marian devotion; Mary; Rosary; clausulae; Contemplation; Chrystus; Maryja; różaniec; kult maryjny; Dominik z Prus; Adolf z Essen; klauzule; kon-templacja; Marialis cultus